Tawakal Sebagai Methode Psikoterapi Terhadap Quarter Life Crisis Perspektif Imam Qusyairi Dalam Risalah Qusyairiyah - Afifah Syafa Nada; Alfi Julizun Az; Heni Indrayani (CV. ITTC INDONESIA, 2024)
ABSTRACT Quarter life crisis occurs in early adulthood because it is a difficult time, because at this point many new problems are faced. One of them is anxiety about the future, confusion of an individual who begins to question career choices, and self-identity and life goals. The purpose of this research was conducted because the phenomenon of quarter life crisis has the potential to exist at least once in the span of human life. This research was conducted in the hope of helping people in the future who experience quarter life crisis. This research is a qualitative research using descriptive analytical method on Imam Qusyairi's thoughts on tawakal in Risalah Qusyairiyah, then analyzed and drawn conclusions based on concrete data. This research is based on library search, research based on various written sources, both in the form of books, journals, articles, or other documents that have relevant and valid data. Imam Qusyairi in Risalah Qusyairiyah explains when Ibn Atha' was asked about the essence of tawakal, he replied “doubts will not arise in you that cause you great difficulty. Therefore you always obtain the essence of tranquility towards the truth you are traveling”. Trusting is a way to deal with quarter life crisis tawakal makes the heart calm, comfortable and peaceful, all the worries, anxiety, anxiety and fear and doubts felt about the future, will be reduced. Tawakal is mandatory for the perfection of faith, there is no faith without trust and there is no trust without faith